Indonesia Analisis Kelayakan Usahatani Padi Sawah di Desa Karangharum Kecamatan Kedungwaringin Kabupaten Bekasi - Agustin, Shifa Ananda; Wagiono, Wagiono; Wijaya, I Putu Eka (Jurnal Ilmiah Wahana Pendidikan, 2024)
Padi plant (Oryza sativa L.) is a very important plant in Indonesia because padi (rice) is the food base. The decline in agricultural land will affect the production of peas in Indonesia. Bekasi district has extensive agricultural lands and becomes one of the fastest economic areas in the field of industry and agriculture. The longer the agricultural sector in Bekasi District begins to experience decline, the greater the impact of economic growth in the industrial sector and agricultural areas increases each year (Hidayah et al, 2022). Increasing the price of fertilizers and increasing the prices of pesticides or herbicides, this increase will surely add to the costs that farmers have to pay (Mustakim, 2023). The research is aimed at analyzing the validity of Usahatani Padi Sawah in Karangharum Village, Kedungwaringin district of Bekasi. Sample determination using Simple Random Sampling technique, divided into two part. Part I has a land area of ≤ 0.5 Ha and Part II has an area of > 0.5 Ha. The research population is 248 farmers and the sample number is 38 farmers. The results of the research on Part I averaged receipts of Rp13.338.750 / season, so the average income of Rp7.541.009 / season. Based on the calculation of R/C Ratio obtained a value of 2.30 > 1 means that the effort is worthy to be carried out. On the Break Event Point calculation obtained BEP production 335.68 kg, BEP Price of Rp2,173 and BEP Acceptance Rp1,678,396. Part II, the average receipt was Rp39,149,167/season, so the average income was Rp22,166,261/season. Based on the calculation of R/C Ratio obtained a value of 2.31 > 1 means usahatani is worthy to be carried out. At the Break Event Point calculation obtains BEP production of 774.46 kg, BEP price of Rp2.169 and BEP Acceptance of Rp3.872.312.